Selection Of The Best Employees Using The Complex Proportional Assessment Method - Widiyawati Widiyawati; Ajeng Sri Widyasih; Sabar Hanadwiputra; Zaenal Mutaqin Subekti; Linda Marlinda (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2023)
Decision Support System for Selection of the Best Employees with the Complex Proportional Assessment (Copras) Method. Awards given by the company to the best employees can encourage every employee to always provide the best performance for the company in carrying out their duties and obligations in the company. Decision-making to determine the best employee can be done by the company by assessing the performance that has been carried out by its employees within a certain period. Evaluation of employee performance at the company is influenced by several criteria, namely performance, work attitude, teamwork, work results, and discipline. The decision support system for selecting the best employees uses the Complex Proportional Assessment (Copras) method, where the decision-making process is carried out by assessing choices based on predetermined criteria. Calculations from the Complex Proportional Assessment (Copras) method yield results, namely the order of importance of the criteria and the best employee recommendations, where the order of the most important criteria starts from performance, work attitude, teamwork, work results, and discipline. As for the results of the research on selecting the best employee, the A7 alternative with a score of 100 is Deni's name